Male crickets adjust ejaculate quality with both risk and intensity of sperm competition - Simmons, Leigh W (The Royal Society, 2007)
Sperm competition theory predicts that males should increase their expenditure on the ejaculate with increasing risk of sperm competition, but decrease their expenditure with increasing intensity. There is accumulating evidence for sperm competition theory, based on examinations of testes size and/or the numbers of sperm ejaculated. However, recent studies suggest that ejaculate quality can also be subject to selection by sperm competition. We used experimental manipulations of the risk and intensity of sperm competition in the cricket, Teleogryllus oceanicus. We found that males produced ejaculates with a greater percentage of live sperm when they had encountered a rival male prior to mating. However, when mating with a female that presented a high intensity of sperm competition, males did not respond to risk, but produced ejaculates with a reduced percentage of live sperm. Our data suggest that males exhibit a fine-tuned hierarchy of responses to these cues of sperm competition.